PENGARUH MINAT BELAJAR DAN KOMPETENSI GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMAN 17 PEKANBARU - Nurjasmi Nurjasmi; Risnawati Risnawati; M. Fikri Hamdani (STAI Darul Qalam Tangerang, 2025)
This research is motivated by less than optimal learning outcomes, low student participation and not optimal competence so that it has an impact on learning outcomes. This study aims to 1) to determine how much influence learning interest has on learning outcomes 2) to determine the effect of teacher competence on learning outcomes 3) to determine the effect of learning interest and teacher competence simultaneously on learning outcomes in Islamic Religious Education subjects Class X SMAN 17 Pekanbaru. This research uses correlational quantitative research. The population in t his study were 95 students of class X. The sample technique of this research is a total sampling of 95 students of class X SMAN 17 Pekanbaru. Data was collected through questionnaires and documentation. Data analysis used descriptive data analysis and hypothesis testing, with learning interest (X1) and teacher competence (X2) as independent variables and learning outcomes (Y) as variables using SPSS version 26. Based on research obtained through a questionnaire 1) students' interest in learning is on an average (Mean) of 127.12 as many as 67% of students are in the medium category. 2) For teacher competence, it is proven by an average of 117.20 as many as 64% of students are in the medium category. 3) There is an influence between learning interest and teacher competence with the learning outcomes of class X SMAN 17 Pekanbaru students as evidenced by the R square test of 0.421 (42.1%) which shows an influence between the independent variable and the dependent variable.